2022
DOI: 10.3390/v14030450
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heparanase Levels in Urine during Acute Puumala Orthohantavirus Infection Are Associated with Disease Severity

Abstract: Old–world orthohantaviruses cause hemorrhagic fever with renal syndrome (HFRS), characterized by acute kidney injury (AKI) with transient proteinuria. It seems plausible that proteinuria during acute HFRS is mediated by the disruption of the glomerular filtration barrier (GFB) due to vascular leakage, a hallmark of orthohantavirus–caused diseases. However, direct infection of endothelial cells by orthohantaviruses does not result in increased endothelial permeability, and alternative explanations for vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…In addition, HS and CS were significantly associated with the death of HFRS in the Kaplan–Meier survival analysis, both of which also demonstrated obvious predictive efficiency for the prognosis (death) of HFRS by the ROC analysis. Interestingly, the expression of heparanase in the urine, plasma, and podocytes of glomerular capillaries was also increased in PUUV-infected patients and was strongly associated with the markers of severity (such as AKI and proteinuria) in HFRS patients ( 37 ). Both of these findings also indicated that there may be destruction and shedding of the glycocalyx in HFRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HS and CS were significantly associated with the death of HFRS in the Kaplan–Meier survival analysis, both of which also demonstrated obvious predictive efficiency for the prognosis (death) of HFRS by the ROC analysis. Interestingly, the expression of heparanase in the urine, plasma, and podocytes of glomerular capillaries was also increased in PUUV-infected patients and was strongly associated with the markers of severity (such as AKI and proteinuria) in HFRS patients ( 37 ). Both of these findings also indicated that there may be destruction and shedding of the glycocalyx in HFRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the patients was assessed with a scoring system based on platelet counts, creatinine values, and mean arterial blood pressure values, as previously describe. 61,62 Two patients scored as severe, while all other scored as mild ( Suppl Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients were stratified as having either mild or severe HFRS based on a scoring system adapted from the sequential organ failure assessment mild. 61,62 As controls, PBMCs were obtained from buffy coats from 10 healthy blood donors from the Blood Transfusion Clinic at the Karolinska University Hospital Huddinge, Stockholm, Sweden (ethical permit nr. 2020-02604) and stored in liquid nitrogen until further use.…”
Section: Patient Samplesmentioning
confidence: 99%
“…The glomerular filtration system bears the brunt of the damage when the kidney experiences ischemia or is exposed to harmful substances [ 40 ]. For instance, podocyte damage, glycocalyx loss and even apoptotic cell death are observed in AKI [ [41] , [42] , [43] , [44] , [45] ] ( Fig.3 B, ii). Renal tubular filtration system lesions allow harmful substances to more easily cross the barrier and accumulate in the renal tubules ( Fig.…”
Section: Overview Of Aki Pathologymentioning
confidence: 99%